Kenya : 2021 Article IV Consultation; Second Reviews Under the Extended Arrangement Under the Extended Fund Facility and Under the Arrangement Under the Extended Credit Facility, and requests for Modifications of Performance Criteria and Structural Conditionality-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Kenya's medium-term economic outlook remains positive, supported by the authorities' continued firm commitment to their economic program amidst a complex environment. Economic recovery is well underway, but Kenya's Sustainable Development Goals (SDGs) have suffered significant setbacks, and poverty has increased. The authorities see the program as providing essential support for sound fiscal management ahead of the 2022 elections, reinforcing their multi-year fiscal consolidation plan to reduce debt vulnerabilities and preserve priority social and development spending.